2014
DOI: 10.1249/mss.0b013e3182a1dc51
|View full text |Cite
|
Sign up to set email alerts
|

A Single Dose of Beetroot Juice Enhances Cycling Performance in Simulated Altitude

Abstract: A single dose of BR lowered V˙O2 during submaximal exercise and enhanced TT performance of trained cyclists in normobaric hypoxia. Consequently, ingestion of BR may be a practical and effective ergogenic aid for endurance exercise at altitude.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
129
5
4

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 130 publications
(157 citation statements)
references
References 34 publications
14
129
5
4
Order By: Relevance
“…These findings are in line with most previous investigations [4,5,22,37], and similar to the results of a recent meta-analysis [6]. The physiological mechanisms underlying the decreased V O2 subsequent to nitrate supplementation have not been fully elucidated, but may be accounted for by: a) an improvement in the efficiency of mitochondrial respiration [35] and/or b) enhanced efficiency of muscle force production [7].…”
Section: Effect Of Nitrate Supplementation On Cardiorespiratory Variasupporting
confidence: 91%
See 4 more Smart Citations
“…These findings are in line with most previous investigations [4,5,22,37], and similar to the results of a recent meta-analysis [6]. The physiological mechanisms underlying the decreased V O2 subsequent to nitrate supplementation have not been fully elucidated, but may be accounted for by: a) an improvement in the efficiency of mitochondrial respiration [35] and/or b) enhanced efficiency of muscle force production [7].…”
Section: Effect Of Nitrate Supplementation On Cardiorespiratory Variasupporting
confidence: 91%
“…Consistent with previous investigations, plasma nitrate and nitrite, and exhaled NO concentrations were significantly elevated following dietary nitrate supplementation [1,2,5,8,55,22,39,38], signifying an increase in the 'substrates' available for NO generation via the nitrate-nitrite-NO pathway [11]. Peak plasma nitrite concentration was 602 % higher in BRJ versus PLA, similar to Arnold et al [38] (775 %) (~ 7 mmol nitrate), but considerably greater than reported by Muggeridge et al [22] (134 %) (~ 5 mmol nitrate) and Vanhatalo et al [8] (150 %) (~ 9.3 mmol).…”
Section: Plasma Nitrate Nitrite and Exhaled Nosupporting
confidence: 90%
See 3 more Smart Citations